Protracted bacterial bronchitis: bronchial aspirate versus bronchoalveolar lavage findings: a single-centre retrospective study - Stijn Verhulst; Lieve Boel; Kim Van Hoorenbeeck (BMJ Publishing Group, 2019)
Retrospective chart review of 133 children who underwent bronchoscopy because of possible protracted bacterial bronchitis to compare the results of bronchial aspirates with those of bronchoalveolar lavage (BAL). When comparing BAL and bronchial aspirate in 70 patients where both samples were available, the result was comparable in 46 cases (65%). If only bronchial aspirates would have been available, seven patients (10%) would have been overtreated, four children (6%) undertreated and three (4%) would have received a different treatment. Although, BAL and bronchial aspirate are comparable in the majority of cases, differences exist with an impact on treatment decision, underlying the uncertainties in the pathophysiology of protracted bacterial bronchitis.